A241 PRICE: PREVENTING READMISSIONS IN IBD CENTRES OF EXCELLENCE. (26th February 2020) - Dang, F; Habashi, P; Gallinger, Z; Nguyen, G C
Abstract: Background: Hospital readmission rates are high in the IBD population, with 20% of patients readmitted within the same calendar year. Hospital discharge processes are not routinely standardized and deficiencies in the transition of care after discharge puts patients at increased risk of illness, hospital utilization and healthcare cost. In addition to increased healthcare expenditure, hospitalizations for IBD patients are associated with nosocomial complications such as venous thromboembolism and infection. Aims: We hypothesize that implementing standardized follow-up by an IBD practice nurse and electronic health outcome monitoring through NoviSurvey can reduce the risk of hospital readmission compared to current approaches of hospital discharge alone. Methods: This parallel randomized control trial is powered for N=400 and will include patients admitted for an IBD flare without requiring surgical intervention from the gastroenterology service or consulted from general internal medicine. Patients randomized to the control arm are discharged with usual standard of care. Patients in the intervention group will be eligible for usual post-discharge care in addition to organized telephone follow-up by an IBD practice nurse at 1, 7 and 30 days post-discharge. In addition, these patients will receive bi-weekly correspondence from NoviSurvey to complete a short questionnaire on clinical disease severity and medication adherence. Based on telephone interaction and survey scores, the IBD nurse may arrange readmission or expedited ambulatory visit for high-risk patients. Results: 15 patients are currently enrolled into our study, with 7 randomized to the intervention and 8 to the control group. In the control group, 25% of patients were readmitted to hospital within 30 days of discharge and 13% failed to follow their steroid taper. There were no patients in the intervention group who were readmitted to hospital within 30 days and none who failed their steroid taper. In both the control or intervention group, there were no occurrences of deep vein thrombosis within 30 days post-discharge. Conclusions: The preliminary findings in our small sample study indicate that a nurse led post-discharge intervention may translate to benefits including decreased readmission rates to hospital, better patient satisfaction and better medication adherence. Funding Agencies: CCC